The subaltern Ulysses - Duffy, Enda. (Minneapolis : University of Minnesota Press, 1994)
Reveals that James Joyce's Ulysses can be seen as a guerrilla text written to resist colonialism.
Introduction: Postcolonialism and Modernism: The Case of Ulysses -- Mimic Beginnings: Nationalism, Ressentiment, and the Imagined Community in the Opening of Ulysses -- Traffic Accidents: The Modernist Flaneur and Postcolonial Culture -- "And I Belong to a Race ... ": The Spectacle of the Native and the Politics of Partition in "Cyclops" -- "The Whores Will Be Busy": Terrorism, Prostitution, and the Abject Woman in "Circe" -- Molly Alone: Questioning Community and Closure in the "Nostos."
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Joyce, James, -- 1882-1941.; Joyce, James, -- 1882-1941 -- Political and social views; Joyce, James, -- 1882-1941; Joyce, James, -- 1882-1941 -- Pensée politique et sociale; Joyce, James, -- 1882-1941; Ulysses (Joyce, James); Politics and literature -- Ireland -- History -- 20th century; Colonies in literature; Ireland -- Politics and government -- 20th century; Ireland -- In literature; Politique et littérature -- Irlande -- Histoire -- 20e siècle.; Colonies dans la littérature.; Irlande -- Politique et gouvernement -- 20e siècle.; Irlande dans la littérature.; Irlande -- Dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Colonies in literature; Literature; Political and social views; Politics and government; Politics and literature; Ireland; Ulysses (Joyce); Postkolonialisme; 1900-1999; History